High‐Performance Semitransparent Organic Solar Cells with Excellent Infrared Reflection and See‐Through Functions. Issue 32 (1st July 2020) - Wang, Di; Qin, Ran; Zhou, Guanqing; Li, Xue; Xia, Ruoxi; Li, Yuhao; Zhan, Lingling; Zhu, Haiming; Lu, Xinhui; Yip, Hin‐Lap; Chen, Hongzheng; Li, Chang‐Zhi
Abstract: Clean energy production and saving play vital impacts on the sustainability of the global community. Herein, high‐performance semitransparent organic solar cells (ST‐OSCs) with excellent features of power generation, being see‐through, and infrared reflection of heat dissipation, with promising perspectives for building‐integrated photovoltaics (BIPVs) are reported. To simultaneously improve average visible transmittance (AVT) and power conversion efficiency (PCE), formally in a trade‐off relationship, of ST‐OSCs, new ternary blends with alloy‐like near‐infrared (NIR) acceptors are employed, which are effective to improve device efficiency while maintaining visible absorption unchanged, resulting in PCEs of 16.8% for opaque devices and 13.1% for semitransparent OSCs (AVT of 22.4% and infrared photon radiation rejection (IRR) of 77%). Further, multifunctional ST‐OSCs are realized via introducing simple, yet effective photonic reflectors, together with optical simulation, leading to not only perfect fitting of the visible transmittance peak (555 nm) to the photopic response of the human eye but also an excellent IRR of 90% (780–2500 nm), along with 23% AVT and over 12% PCE. This is thought to be the best‐performing multifunctional ST‐OSC with promising prospects as BIPVs in terms of power generation, heat dissipation, and being see‐through. Abstract : High‐performance semitransparent organic solar cells are achieved through combined design efforts on the formulation of near‐infrared ternary blends and optical control over photonic reflectors, which exhibit excellent features of power generation, they being see‐through, and infrared reflection.